(untitled) (Società e diritti, 2023)
The reform of Title V of the Constitution and the introduction of the principle of subsidiarity have consolidated the role of the Third sector in the Italian legal system. The Third sector, placing itself on the level of horizontal subsidiarity, acquires a political relevance in civil society as an opportunity for participation. Even in the National Recovery and Resilience Plan, the Third sector has an important role. Therefore, it is interesting to analyze what are the most recent Third sector perspectives, especially for environment protection and energy. In this regard, the participation of the Third sector in the foundation of energy communities deserves a deepening, not only in the Italian legal system but in other European legal systems too.